RF 1090 MHZ BAND LOAD MODEL (Perner's Contacts, 2014)
Nowadays, the load of 1090 MHz frequency represents a key factor determining the quality of surveillance application in terms of air traffic control. Although there is an intention to provide more surveillance data on 1090 MHz, an uncontrolled access to the frequency is one of the aspects limiting to do so. In fact, with an increasing number of transmitted messages, the loss of information during the decoding on receipt is more probable due to the garbling or overlapping effect. Firstly, this text will discuss the use of the radio frequency of 1090 MHz with regard to the aeronautical traffic. Then, it will represent an approach to radio frequency load measurement using computer based modelling. Finally, model RFLM 2014 that was created will be described in a greater detail together with results for a FIR of the Czech Republic.